2020
DOI: 10.1371/journal.pone.0235188
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the characteristic temperament of cats on the emotions and hemodynamic responses of humans

Abstract: Cats positive effects on their owners' physiological and psychological health, including improved mood and activation of the human prefrontal cortex and inferior frontal gyrus in the brain. However, the association between the health benefits provided by cat ownership and the characteristic behaviors and reactions of cats is unclear. We recruited 29 participants to measure human prefrontal cortex activity, using functional near-infrared spectroscopy, during interactions with a cat. After the experiments, parti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 48 publications
1
15
0
Order By: Relevance
“…The functional components obtained from HMS have been shown to be highly coincident with signals estimated by MPAM in previous studies using body tilting, breath holding and finger tapping tasks [53, 55]. HMS has been applied to studies of children and adults using the same equipment as in the present study [33, 34, 56–60].…”
Section: Methodssupporting
confidence: 54%
See 1 more Smart Citation
“…The functional components obtained from HMS have been shown to be highly coincident with signals estimated by MPAM in previous studies using body tilting, breath holding and finger tapping tasks [53, 55]. HMS has been applied to studies of children and adults using the same equipment as in the present study [33, 34, 56–60].…”
Section: Methodssupporting
confidence: 54%
“…The head module incorporated six sources and six detectors arranged alternatively at a probe distance of 30 mm, resulting in 16 channels (Figure 2). The probe plane was placed on the forehead with Fpz in the international 10 to 20 system as the lowest center [32], according to previous studies targeting the prefrontal area of adults using the same CW-fNIRS equipment [33,34]. The probe and channel locations were spatially registered to the Montreal Neurological Institute standard brain space following the virtual registration method using similar CW-fNIRS equipment as this experiment [35].…”
Section: Measurementsmentioning
confidence: 99%
“…In addition, by summarizing the emotional profile, the highest number of participants showed the highest valence when the dog group was evaluated, followed by the cat and pig groups. It was reported that the individuals’ valence showed a positive correlation with the success rates for interactions with the pet, especially during training and play interactions [ 28 ]. However, the characteristic temperament of a pet may be the key factor to the mechanism underlying the positive health effects gained through pet ownership.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to dogs, cats have become a popular companion animal for humans with positive effects on the pet owner’s health [ 27 , 28 , 29 , 30 , 31 ]. It was reported that the factors related to the quality of dog–owner relationships differ from those of cat–owner relationships [ 32 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation